2023
DOI: 10.3390/en16114312
|View full text |Cite
|
Sign up to set email alerts
|

Use of Artificial Neural Networks to Model Biomass Properties of Miscanthus (Miscanthus × giganteus) and Virginia Mallow (Sida hermaphrodita L.) in View of Harvest Season

Abstract: Miscanthus and Virginia Mallow are energy crops characterized by high yields, perenniality, and low agrotechnical requirements and have great potential for solid and liquid biofuel production. Later harvest dates result in lower yields but better-quality mass for combustion, while on the other hand, when biomass is used for biogas production, harvesting in the autumn gives better results due to lower lignin content and higher moisture content. The aim of this work was to determine not only the influence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…In the present study, the carbon content of Sida biomass was bound by a weak, but significant, correlation with the HHV. Carbon concentration was similar to that noted by Stolarski et al [42] and Šurić et al [38], and it was higher than that reported by Šiaudinis et al [43]. In the work of Bilandžija et al [37], carbon concentration was much lower when Sida biomass was harvested in January (32.22% DM) than in November and March (46.79% and 50.08% DM, respectively).…”
Section: Evaluation Of the Elemental Composition Of Virginia Fanpetal...supporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, the carbon content of Sida biomass was bound by a weak, but significant, correlation with the HHV. Carbon concentration was similar to that noted by Stolarski et al [42] and Šurić et al [38], and it was higher than that reported by Šiaudinis et al [43]. In the work of Bilandžija et al [37], carbon concentration was much lower when Sida biomass was harvested in January (32.22% DM) than in November and March (46.79% and 50.08% DM, respectively).…”
Section: Evaluation Of the Elemental Composition Of Virginia Fanpetal...supporting
confidence: 82%
“…In other studies, the HHV and LHV of Virginia fanpetals biomass varied across years, and minor differences resulting from the harvest date (fall, winter, early spring) were noted [9,34,35,37,43,44]. The HHV and LHV of the biomass were generally higher when Virginia fanpetals was harvested in the spring rather than in the fall [38], but these trends varied [34,37]. Szyszlak et al [45] observed that the HHV was affected by the thickness of Virginia fanpetals shoots and suggested that the value of this parameter could be influenced by plant density.…”
Section: Evaluation Of the Thermophysical Properties Of Virginia Fanp...mentioning
confidence: 71%
See 1 more Smart Citation
“…The application of the ML model in the estimation of HHV biomass shows clear advantages in terms of accuracy and reliability of predictions. Models such as ANNs often achieve high R 2 values (>0.90) and lower RMSE and MAE values, demonstrating their ability to estimate by managing the data [46,47]. On the other hand, it should be noted that although high accuracy and lower modeling errors are achieved, longer runtimes are often required due to higher learning complexity [48], which can be a limiting factor when computational resources are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The output value, denoted as Y , is determined by transfer functions, with f 1 representing the transfer function for the hidden layer and f 2 for the output layer. The input layer matrix is denoted by X [ 32 , 33 ]: …”
Section: Methodsmentioning
confidence: 99%